Contextual interference in children with brain lesions: a pilot study investigating blocked vs. random practice order of an upper limb robotic exergame - Graser, Judith V. (Pilot Feasibility Stud, 2021)
INTRODUCTION: Evidence about contextual interference in children with brain lesions when practising motor tasks is lacking. Our main objective was to evaluate the feasibility of a randomised controlled trial (RCT) comparing blocked with random practice order of an upper limb robotic exergame to improve reaching in children with neuromotor disorders with a pilot trial. METHODS: We recruited children with brain lesions and impaired upper limb functions who underwent a 3-week schedule that consisted of baseline assessments, intervention period (participants were randomised to a blocked or random order group), and follow-up assessment. We evaluated ten feasibility criteria, including the practicability of the inclusion/exclusion criteria, recruitment rate, feasibility of randomisation, scheduling procedure, and the participants’ programme adherence. RESULTS: The inclusion/exclusion criteria were not completely feasible as patients who were not able to perform the exergames were included. Twelve participants were recruited, and six datasets were used for analysis. The scheduling and randomisation procedures were generally feasible, but the procedure was only partially feasible for the participants, as some sessions were aborted due to lack of motivation and fatigue. CONCLUSION: An RCT following this study protocol is not feasible. We formulated suggestions for future studies that aim to investigate contextual interference as in this pilot study. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02443857, registered on May 14, 2015 SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40814-021-00866-4.